PENGEMBANGAN HIDROGEL ALGA HIJAU Spirogyra sp SEBAGAI DESALINASI AIR PAYAU DENGAN DI PANTAI TANJUNG PAKIS KARAWANG - Sudrajat Sugiharta; Farid Ahmad; Nia Yuniarsih (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Communities around the coast of Tanjung Pakis Karawang still consume a lot of brackish water for drinking, cooking and toilet purposes. Long-term use of brackish water will have detrimental effects on health. Brackish water contains high levels of salinity, total dissolved solids, total suspended solids, and mineral levels. There are various ways to improve brackish water quality so that it can be consumed, including hydrogel biosorption. This research aims to determine the level of desalination capability in brackish water, including testing temperature, pH, salinity, TDS, TSS using the green algae Spirogyra sp hydrogel, which is capable of desalination to improve water quality. This research uses a quasi-experimental method by comparing hydrogel preparations with powders and granules and using a zeolite comparison standard as a positive control. Hydrogel preparations are made with percentages of 0%, 2%, 4% and 6%. The organoleptic results showed that the hydrogel preparation had a dense texture and a distinctive odour of green algae with a dark green colour. The hydrogel preparation has a stable viscosity value in the H2 preparation, with a pH value that follows water quality standards (6.5-8.5). This hydrogel preparation has a good swelling value found in the H2 preparation. It has a high fraction value in the H4 preparation. Desalination data were analyzed using the ANOVA test. This research concludes that the green algae hydrogel preparation can desalinate brackish water based on the results of temperature, TSS and salinity tests compared with Zeolite and Hydrogel without algae in the three samples.